Leadership Style and Traits Practice by the Contractors in Managing Construction Projects in Sarawak, Malaysia - Rantai, Rodrick anak; Omar, Roshartini; Sarpin, Norliana (Research in Management of Technology and Business, 2022)
Managing construction projects with a lack of leadership spirit can weaken the organization's ability to deal with challenges in the construction industry. Leadership necessarily requires influence in order to complete missions and provide guidance for a more well-organized and practical organisation. Positive leadership was responsible for nearly 76 percent of project success, while negative or poor leadership was responsible for 67 percent of project failure. As a result, the need for quality leadership to steer construction project success is undeniable. With appropriate leadership among the construction parties, the construction process can be navigated in a sustainable manner. As a result, the goals of this study are to investigate the leadership style, leadership quality / traits, and method to improve leadership competencies that should be implemented in Sarawak construction projects. This study was conducted on construction sites in Sarawak. The contractors are the respondents. 95 out of 118 respondents completed the Google form to respond to the question on the questionnaire that was shared online. The response rate was around 80%. The information is gathered quantitatively. The questionnaire data is then quantitatively analysed using the Statistical Package for the Social Sciences (SPSS) version 26 before being converted to graphical, chart, and table formats. According to the findings of this study, the transactional leadership style is the most prevalent in the Sarawak construction industry. The most desired leadership traits and qualities are honesty and dependability. The most favorable method to improve leadership competencies is a leader should have a capability to come out with a strategic action. In conclusion, a good leadership style is a must in order for the businesses to be excellent.